The use of Communicative Language Teaching (CLT) Approach to develop L2 Speaking Proficiency at Vocational Students in South Aceh Polytechnic - Jannah, Dina Miftahul; Bean, Hasbaini (JATAED: Journal of Appropriate Technology for Agriculture, Environment, and Development, 2024)
Many information and knowledges delivered in English. To support students’ skill, the vocational students in South Aceh Polytechnic are required to learn English in each semester. Learning English as a second or foreign language (L2) is so challenging for the students. They find problems in producing target language. A special challenging is oral communication.  Difficult Speaking habits such as lack of grammar knowledge and vocabulary, poor pronunciation skills, lack of confident to start speaking with more competent speakers of English. Therefore, the researcher conducted the research in South Aceh Polytechnic to increase students’ speaking ability by teaching them using Communicative Language Teaching (CLT) approach. This study discussed the nature of L2 speaking with the development of communicative skills. The methodology of this study was an experimental research which used quasi experimental design. This research was conducted especially for computer engineering students which consisted of 39 students as a sample. There were two classes, one class as an experimental group and another class as a control group.  The teacher gave treatment in experimental group by providing relevant context in learning target language, and the researcher also wanted to know their responses toward the CLT Approach. The instruments that used by the researcher in this study was pretest, posttest, and questionnaire. The result of this study showed that there are any significant differences between the students who are given treatment. It proved by the student scores in posttest. In essence, this approach effectively helped students in enhancing L2 speaking proficiency and encourage their confident in speaking.